Perancangan Infrastruktur VoIP Menggunakan Trixbox Open Source dengan Lapisan Keamanan VPN Antar Klien - Djumhadi Djumhadi; Tukino Tukino (Prosiding, 2023)
PT Batam Bintan Telekomunikasi has several employees scattered across various rooms, and effective communication among them is crucial. Previously, the company relied on a Private Automatic Branch Exchange (PABX) phone system, which proved suboptimal as each room had only one PABX line while accommodating eight employees. Consequently, there was a need to optimize the communication system for PT Batam Bintan Telecommunication employees. The communication system was enhanced by implementing Voice over Internet Protocol (VoIP) as a replacement for the PABX system. VoIP was deployed using a Trixbox server, SIP phones, Zoiper, and MicroSIP applications for making calls on client computers, with VPN (Virtual Private Network) ensuring security between clients. Each employee was provided with a VoIP account registered on the Trixbox server, complete with a telephone number and password. Based on the research findings, the implementation of VoIP on computers within PT Batam Bintan Telekomunikasi's environment, connected through the Trixbox server, significantly facilitated communication among employees, ultimately supporting their performance. This VoIP solution is expected to replace the previous communication system utilized at PT Batam Bintan Telekomunikasi, thus leveraging internet resources to enhance communication efficiency.